2020
DOI: 10.3390/f11020159
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the Survival of Tropical Forest Fragments in Xishuangbanna, Southwest China

Abstract: Research Highlights: The reasons for persistence of forest fragments in human-dominated landscapes have rarely been examined, despite their importance in biodiversity and ecosystem services. We determined these reasons for forest fragments on collective land in Xishuangbanna prefecture, southwest China. Background and Objectives: Reconciling economic development with biodiversity conservation has been a major challenge in China’s small tropical land area, where local realities have often been in conflict with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…These highlighted plants include 15 threatened or endangered species, 17 species with UV value over 0.9 and 19 species consumed by both humans and elephants. The environmental, cultural, and religious benefits of the forest are generally recognized by the local people [66]. By learning the ethnobotanical knowledge from the ethnic groups and encouraging them to cultivate more plants, especially the endangered species, in the community land and individual households retained forest, as well as their homegardens could open a new channel for connecting the fragmented forest as a whole, then contributing to conservation and the sustainable use of natural resources.…”
Section: Traditional Cultivated Plant Genetic Resources and Diversified Agriculturementioning
confidence: 99%
“…These highlighted plants include 15 threatened or endangered species, 17 species with UV value over 0.9 and 19 species consumed by both humans and elephants. The environmental, cultural, and religious benefits of the forest are generally recognized by the local people [66]. By learning the ethnobotanical knowledge from the ethnic groups and encouraging them to cultivate more plants, especially the endangered species, in the community land and individual households retained forest, as well as their homegardens could open a new channel for connecting the fragmented forest as a whole, then contributing to conservation and the sustainable use of natural resources.…”
Section: Traditional Cultivated Plant Genetic Resources and Diversified Agriculturementioning
confidence: 99%
“…The following was discussed based on the abovementioned analyses: Previous studies [ 78 , 79 , 80 ] indicated that rubber plantations and tea plantations replaced Xishangbanna’s most biodiverse native forests due to local priority policies. National policies to protect native forests from clearance and overexploitation, or to encourage reforestation, are interpreted at a local level by county and village officials.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have highlighted the importance of conserving and sometimes restoring forest fragments in Xishuangbanna (e.g., Liu and Slik 2014; Zhang et al 2019, 2020), as well as encouraging appropriate financial incentives (e.g., Xi 2009;Yi et al 2014; Zhang et al 2020), which require working with local communities. In 600 households across nine ethnic groups (including Dai) in Xishuangbanna, Zhang et al (2020) found that 93% of communities maintained a collective forest, and 96% of the time it was for cultural or religious reasons. However, much of the literature on sacred groves paints them as unchanging remnants of ancient forest, thereby erasing how the peoples who protect them have long negotiated the meanings of sacred nature and maintenance of sacred groves with other forms of land use shaped by state and market pressures (Dove et al 2011; Zeng 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Although Zhu et al (2010) and Liu (2016) investigated shifts in species composition (including shifts in shade-tolerant and heliophilic species) over time in one Holy Hill by comparing species inventory data from 1950/1960 to data from 1997 and 2008, their analyses were based on presence/absence data and lacked data on species abundance and dominance to detect phytosociological changes in species composition and to explain why these changes were occurring, nor do they provide information on species population persistence based on regeneration. Similarly, though Holy Hills are also occasionally included with other kinds of forest fragments as part of larger landscape-level analyses (e.g., Liu and Slik 2014; Pasion et al 2018; Zhang et al 2020), none have conducted in-depth examinations of regeneration and community dynamics.…”
Section: Introductionmentioning
confidence: 99%